Stem cells: knowledge and attitude among health care providers in Qassim region, KSA - Tork, Hanan; ALRaffaa, Safiah; ALMutairi, Khadija; ALShammari, Noof; ALHarbi, Amani; ALOnzi, Awatef (International Journal of Advanced Nursing Studies, 2017)
Background: Health care providers as a trusted source of information for most patients should be able to provide counseling services to patients on the new concept of stem cells utilization, benefits and its practice implications.Objective: this study aims to assess the knowledge and attitude of health care providers in Qassim region regarding stem cells.Methods: Self-administered tools were utilized among 250 health care providers were chosen from five major hospitals in Qassim, including doctors, nurses, and other health care providers such as pharmacists, dietaries and administrative staff.Results: The participants were female,<30 years in age, had practiced for <10 years and nurses. About 56% of respondents had a moderate knowledge regarding stem cells, and only 31.2 % had good knowledge. About three quarters 191 (76.4%) of the participants exhibited positive attitude towards stem cells use. A Pearson’s correlation between knowledge and attitude scores was statistically significant. Conclusion: Data from the present study revealed the moderate levels of knowledge and positive attitude toward stem cells and its application among health care providers in Qassim. Therefore, this study suggests that educational programs on stem cells should be implemented to improve stem cells knowledge and encourage a more positive attitude.